Green Solutions: Integrating Small and Medium- sized Enterprises in Global Value Chains - Krishn A. Goyal; Teena Mertiya (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
The real-life instances call for new perspectives about stimulating SMEs' success and increasing their involvement in Global Value Chains. Although it is hard to isolate typical SME patterns across sectors and regions. SMEs must have exposure to GvCs linked with green innovative services. Following the development of Green Technology e.g. AI, SMEs may significantly contribute to equitable and inclusive transformations and encourage sustainable business operations. Precisely it is the result of greater awareness and access to data, business circles, technology at our fingertips, and human capital improvements. The primary finding of this study is that small and medium-sized enterprises that sustain themselves in the face of strong global competition are likely to see their operations develop over time. The key aspect of achievement remains chain- wide partnerships.